Association between HBA1C and Coronary Artery Disease Severity in patients of Diabetes Mellitus Type 2 presented as Acute Coronary Artery Syndrome and Non Diabetic - Mahboob Qadir, Muhammad Shahid Nawaz Khan, Humayun Riaz Khan, Nadeem Ullah, Muddasar Ahmed, Hafiz Muhammad Farhan Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: to investigate the prevalence of diabetes mellitus type 2 (T2DM) and association of HbA1c with the severity of coronary artery disease (CAD) in patients presenting at tertiary care center as acute coronary syndrome and non-diabetic. Study Design: Prospective observational study Duration and Place Study was conducted at department of general medicine Nishter Hospital, Multan from January 2021 to January 2022 in 1 year duration. Methodology: A total of 200 patients were enrolled in study. Main variables of study were BMI, smoking status, dyslipidemia, hypertension, STEMI, angina, HbA1c and treatment strategy. SPSS version 23 was used for data analysis. P value below or equal to 0.05 was taken as significant. Results: Among total 83.5% patients intervened by therapeutic, whereas 48.0% used thrombolytic drug in STEMI. 70.7% patients were thrombolysis in therapeutic intervention and 44.8% were streptokinase in thrombolytic drug. In fasting blood sugar, 53.0% patients were diabetic, whereas in HbA1c levels, 52.3% patients were diabetic. Conclusion: This study highlights the significance of testing for diabetes in individuals in poor nations who report with non-diabetic acute coronary syndrome. One of manifestations of diabetes mellitus may be the acute coronary syndrome. Keywords: Acute coronary syndrome, Coronary angiography, Diabetes, HbA1c.